A two-level model for describing the nonisothermal deformation of two-phase polycrystals - Trusov, Petr Valentinovich; Kondratev, Nikita Sergeevich (Computational Continuum Mechanics, 2014)
Over the last few decades, two-phase austenitic-ferrite (duplex) steels have found wide application in many industries. Duplex steels have unique properties compared to the individual phases of the polycrystalline material. The essential feature of high-temperature deformation of this class of materials is softening processes, which provide the high ductility of polycrystals. Because a ferrite phase has high stacking fault energy (SFE), there occurs dynamic recovery, and in an austenitic phase with low SFE the relaxation of elastic stresses is attained during recrystallization. The paper uses an urgent approach to the description of plastic deformation which enables us to consider in explicit way the physical mechanisms of inelastic deformation at the scale levels lower than the macroscopic level. The main deformation mechanism for this class of materials is the slipping of edge dislocations over the crystallographic planes and directions. The effect of temperature on the mobility of dislocations is examined. The basic physical mechanisms of crystal hardening due to the interaction of mobile dislocations with forest dislocations, barriers of the Lomer-Cottrell type and grain boundaries are taken into account. The softening mechanisms associated with recovery and recrystallization are described. The paper considers the modification of a physical two-level model describing the high-temperature deformation of duplex steels. A mathematical formulation for each level is presented. An algorithm for numerical implementation of the proposed model is given. Simulation results are in good qualitative agreement with experimental data.
Keywords: crystal plasticity; duplex steels; softening of slip systems; dynamic recovery; recrystallization